Germany - Schulte-Peevers, Andrea; Christiani, Kerry; Di Duca, Marc; Le nevez, Catherine; Masters, Tom; Ver Berkmoes; Walker, Benedict (Footscray, Victoria, Australia Lonely Planet Publications Pty Limited, 2016)
Lonely Planet Germany is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. See storybook castles arise from the Bavarian forest, raise a stein to an oompah band in a Munich beer garden, and take in the vibrant Berlin arts scene; all with your trusted travel companion. Get to the heart of Germany and begin your journey now!
At head of title: Lonely Planet
Includes the pull-out map Berlin City, top sights in full detail, expert recommendations.
Includes bibliographical references, filmography and index.
Keywords: Germany -- Guidebooks; Germany -- Description and travel